Real ethics : reconsidering the foundations of morality - Rist, John M. (Cambridge University Press, 2002)
In this book, John Rist offers a vigorous defence of an ethical theory based on a revised version of Platonic realism. His lively and accessible study is informed by a powerful sense of philosophical history, and will be of interest to both students and scholars of ethics.